Effects of a foliar fertilizer containing boron on the development of Sclerotinia stem rot (Sclerotinia sclerotiorum) on canola (Brassica napus L.) leaves. Issue 1 (28th October 2019) - Ni, Li; Punja, Zamir K.
Abstract: Sclerotinia stem rot ( Sclerotinia sclerotiorum Lib. De Bary) is one of the most destructive fungal diseases on canola ( Brassica napus L.). The effect of a foliar fertilizer containing 3% boron (Active Flower™ [AF]) in reducing disease severity was evaluated. AF at 0.1, 0.3 and 0.5 ml/100 ml was first tested for growth inhibition of S. sclerotiorum in potato dextrose broth. Growth was reduced at 0.5 ml/100 ml by around 90%. Boric acid (BA), an important component of AF, was tested against fungal growth at 10 ml/L, and no significant effect ( p  = .05) was found. Foliar applications of AF and AF formulation that did not contain boron at 0.1, 0.3 and 0.5 ml/100 ml were made weekly to canola 'Westar' grown under greenhouse conditions. Treatments were also made with BA at 10 ml/L to canola plants. After four applications, AF at 0.5 ml/100 ml and BA at 10 ml/L enhanced boron levels in leaves by fivefold and threefold, respectively, compared with the control. Lesion size of S. sclerotiorum on detached leaves was significantly ( p  < .05) reduced by AF at 0.5 ml/100 ml, but lesion size was not reduced on AFWB‐treated leaves. Experiments were repeated twice with the same results. Levels of phenolic compounds in leaves treated with 0.5 ml/100 ml AF were enhanced by twofold compared with the control. There were no significant differences in lignin, peroxidase (POD) or polyphenoloxidase (PPO) between the control and AF treatments. These results suggest that enhanced boron levels in canola leaves were associated with a suppressive effect on disease due to S. sclerotiorum .